Synergistic Activity of New Diclofenac and Essential Oils Combinations against Different Candida spp. - Antonio Rosato; Elisabetta Altini; Sabina Sblano; Lara Salvagno; Filippo Maggi; Giuliana de Michele; Alessia Carocci; Maria Lisa Clodoveo; Filomena Corbo; Giuseppe Fracchiolla (Antibiotics, 2021)
According to recent studies, Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) have shown a good antimicrobial and antifungal activity. Their association with essential oils (EOs) could be useful for the treatment of infections caused by Candida spp. The aim of this studyis to evaluate the synergistic antifungal activity of new combinations between Diclofenac Sodium Salt (DSS), a widely used NSAID, with EOs of Mentha × piperita, Pelargonium graveolens and Melaleuca alternifolia. The in-vitro antifungal activity was determined on different Candida strains. The determination of the chemical composition of EOs was carried out by gaschromatography-massspectrometry (GC-MS). Susceptibility testing of planktonic cells was performed by using the broth microdilution assay and checkerboard methods. Minimum Inhibitory Concentrations (MIC) of DSS was in a range from 1.02 to 2.05 μg/mL reaching a MIC value of 0.05 μg/mL when combined with Pelargonium graveolens (FICI = 0.23–0.35) or Menthapiperita (FICI = 0.22–0.30) EOs. These preliminary results show thatthe combination of the EOs with DSS improves the antifungal activity on all the tested Candida strains.